Organic synthesis of high added value molecules with MOF catalysts - Martín, Nuria; Cirujano, Francisco G (Organic & biomolecular chemistry, 2020)
Recent examples of organic synthesis of fine chemicals and pharmaceuticals in confined spaces of MOFs are highlighted and compared with silica-based ordered porous solids, such as zeolites or mesoporous (organo)silica. These heterogeneous catalysts offer the possibility of stabilizing the desired transition states and/or intermediates during organic transformations of functional groups and (C-C/C-N) bond forming steps towards the desired functional high added value molecular scaffolds. A short introduction on zeolites, mesoporous silica and metal-organic frameworks is followed by relevant applications in which confined active sites in the pores promote single or multi-step organic synthesis of industrially relevant molecules. A critical discussion on the catalytic performances of the different types of hybrid inorganic-organic catalysts in the synthesis of O- and N-containing acyclic and heterocyclic molecules has been presented.Recent examples of organic synthesis of fine chemicals and pharmaceuticals in confined spaces of MOFs are highlighted and compared with silica-based ordered porous solids, such as zeolites or mesoporous (organo)silica. These heterogeneous catalysts offer the possibility of stabilizing the desired transition states and/or intermediates during organic transformations of functional groups and (C-C/C-N) bond forming steps towards the desired functional high added value molecular scaffolds. A short introduction on zeolites, mesoporous silica and metal-organic frameworks is followed by relevant applications in which confined active sites in the pores promote single or multi-step organic synthesis of industrially relevant molecules. A critical discussion on the catalytic performances of the different types of hybrid inorganic-organic catalysts in the synthesis of O- and N-containing acyclic and heterocyclic molecules has been presented.